2015
DOI: 10.2135/cropsci2014.09.0625
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Remote Green: Red Perpendicular Vegetation Index Ground Cover Fraction Estimation in Cotton

Abstract: Abbreviations: DC, digital count; GC, ground cover; GCF, ground cover fraction; GCF PixelCount , ground cover fraction of soil removal based on individual pixel values; GCF PVI-Green , ground cover fraction estimate based on average green and red reflectance; LAI, leaf area index; NIR, near-infrared; PVI, perpendicular vegetation index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…The high irrigation treatments had differences in NAWF among different cultivars, but maximum NDRE values occurred with canopy closure, rather than when the crop had completed growth. Sharma et al (2015b) observed that ground‐cover fraction approached 1.0 as the crop reached complete canopy coverage in the higher irrigation treatments. Ritchie et al (2010) reported similar results, where NDRE was insensitive to changes in ground cover fraction as it approached 1.0, and Ritchie and Bednarz (2005), where NDRE was insensitive to leaf area index values >2.0.…”
Section: Resultsmentioning
confidence: 96%
“…The high irrigation treatments had differences in NAWF among different cultivars, but maximum NDRE values occurred with canopy closure, rather than when the crop had completed growth. Sharma et al (2015b) observed that ground‐cover fraction approached 1.0 as the crop reached complete canopy coverage in the higher irrigation treatments. Ritchie et al (2010) reported similar results, where NDRE was insensitive to changes in ground cover fraction as it approached 1.0, and Ritchie and Bednarz (2005), where NDRE was insensitive to leaf area index values >2.0.…”
Section: Resultsmentioning
confidence: 96%
“…Sharma et al. (2015a) observed that ground cover fraction, which is the number of pixels containing vegetation versus scene (vegetation and soil pixels), approached 1.0 as the crop reached complete canopy coverage in the higher irrigation treatments. Ritchie et al.…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of growth and development in cotton ( Gossypium hirsutum L.) relies on the measurement of phenotypic characteristics such as leaf structure, leaf area index (LAI), leaf and canopy temperature, and canopy height (Sharma, Ritchie, & Rajan, 2015a; Wiegand, Richardson, Escobar, & Gerbermann, 1991). Most of these measurements have traditionally been conducted on a small‐scale level due to the intensive labor requirements (Rahaman, Chen, Gillani, Klukas, & Chen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…FVC were calculated effectively from an orthomosaic image with hundreds of three-channel RGB images by separating and classifying vegetation pixels from soil pixels and other non-vegetation pixels (Guo et al 2013;Sharma et al 2015) as demonstrated by (Duan et al 2017). FVC is the ratio of the vertical projected area of vegetation to the total ground area (Lin and Qi 2004).…”
Section: Calculation Of Fvcmentioning
confidence: 99%